Serial volumetric assessment of large for size liver grafts after whole cadaveric liver transplant in adults: do large liver grafts shrink in size?. Issue 2 (February 2016) - Bekheit, Mohamed; Rajakannu, Muthukumarassamy; Bucur, Petru; Adam, Rene; SaCunha, Antonio; Castaing, Denis; Cherqui, Daniel; Vibert, Eric
Abstract: Background: After whole graft orthotopic liver transplantation (OLT), adaptation of the large grafts' volume to recipient weight is widely accepted despite the paucity of evidence on this subject. Methods: Thirty nine patients with GRWR > 2.5% were included in this study and subsequently divided into two groups with 3 ≥ GRWR > 3%. Patients had CT scans at three predetermined time points after OLT used for measuring the liver volume. The objective of this study is to evaluate the volumetric changes of whole large liver grafts after adult OLT. Results: At LT, the mean graft recipient body weight ratio (GRWR) was 3.1 ± 0.4%. The mean liver weight was 1881 ± 68 g at LT, 2014 ± 99 ml at one week, 1725 ± 126 ml at 3 months, and 1632 ± 117 (ml) at >6 months. There is an initial increase at 1 week after LT and a subsequent decrease of liver volume on later measurements. None of the late volume measurements were significantly different from the initial graft volume at liver transplant in pair wise comparisons ANOVA repeated measures (p > 0.05). Similarly, the mean GRWR did not change significantly between the initial calculation at transplantation date and the subsequent measurements during the different study time points (F = 0.04, p = 0.96) with a mean of 3.1% (95% CI = 2.2–4.2). AUC ROC discriminated a cutoff of 3% for the initial GRWR above which grafts tend to decrease in size over time (c statistics = 0.74, p = 0.036). In a Clustered ANOVA repeated measures, there was no significant difference in the changes of liver volume between both groups. However, patients with GRWR > 3 showed a trend towards a latent reduction in volume over the tracing period. There was a tendency, but none significant; towards a higher bilirubin, AST, ALT levels over the first postoperative days in recipients with GRWR > 3. Conclusion: Large grafts do not significantly decrease in size. Nonetheless, grafts weighing >3% of the GRWR show a different trend towards decrease in size over time.